HLA common and well‐documented alleles in China. (25th September 2018) - He, Y.; Li, J.; Mao, W.; Zhang, D.; Liu, M.; Shan, X.; Zhang, B.; Zhu, C.; Shen, J.; Deng, Z.; Wang, Z.; Yu, W.; et al.
Abstract : The American Society for Histocompatibility and Immunogenetics HLA common and well‐documented (CWD) catalog, CWD 2.0.0 catalog and European Federation for Immunogenetics (EFI) CWD catalog have been published, which are useful for improving the accuracy of HLA genotyping in laboratories. Here, we studied the Chinese HLA CWD catalog. A total of 812 211 unrelated volunteer donors from the China Marrow Donor Program (CMDP) were analyzed. Six hundred seventy‐six alleles at the HLA‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 loci were defined as CWD alleles in the Chinese population, including 159 common and 517 well‐documented alleles. The distribution of HLA alleles in the Chinese CWD catalog is different from that in the EFI CWD catalog. Thirty‐two percent (215/676) of CWD alleles in the Chinese CWD catalog are shared with those in the EFI CWD catalog. Fifty‐six percent (380/676) of alleles in the Chinese CWD catalog are not found in the EFI CWD catalog, while 655 alleles in the EFI CWD catalog are neither common nor well‐documented alleles in the Chinese CWD catalog. The Chinese CWD catalog described in this study may help to improve high‐resolution histocompatibility testing for CMDP‐accredited laboratories in China. However, to accommodate an increasing number of HLA alleles, this Chinese CWD catalog should be regularly updated.